Menopausal status and the risk of lung cancer in women: A PRISMA-compliant meta-analysis. Issue 26 (June 2017) - Min, Lingfeng; Wang, Fang; Liang, Sudong; Yang, Junjun; Xu, Xingxiang
Abstract: Background: Quantification of the association between menopausal status and risk of lung cancer is inconsistent. We carried out a meta-analysis of available studies to examine this issue. Methods: Relevant articles were identified by searching PudMed and Embase databases. Reference lists from selected papers were also reviewed. A random-effect model was used to calculate summary odds ratios (OR) and relative risk (RR) with 95% confidence interval (CI). Publication bias was estimated using Egger regression asymmetry test. Results: Eight eligible studies, including 5 case–control studies and 3 cohort studies, provided data for meta-analysis. Postmenopausal women had a statistically significant increased risk of lung cancer in all included studies (RR = 1.44, 95% CI: 1.12–1.85) and cohort studies (RR = 1.39, 95% CI: 1.05–1.86), but not in case–control studies (OR = 1.46, 95% CI: 0.95–2.24). Conclusions: Overall, there was evidence that postmenopause is related to increased lung cancer risk. However, studies have produced slightly heterogeneous results ( I 2 = 38.40%). To obtain a better indication of relationship, well-designed large prospective studies are required.